Examination of Dyeing Properties of the Dyed Organic Cotton Knitting Fabrics Using Yarrow (Achillea Biebersteinii AFAN and Achillea Millefolium L.) - Recep Karadag; Yusuf Yildiz (Journal of Natural Fibers, 2022)
In this study, organic cotton knitting fabrics were dyed with yarrows (Achillea biebersteinii and Achillea millefolium L.). The fabric samples were separately dyed with flowers and leave-stems of yarrows – alum and yarrow – alum – gall oak. A reverse-phase high-performance liquid chromatography with diode-array detection method was utilized for the identification of the coloring compounds of dyes in the dyed fabrics and the plant extracts. The extraction of dyes was carried out with a hydrogen chloride ⁄ methanol ⁄ water (2:1:1; v⁄v⁄v) mixture. Keampferol-O-glucoside, axillarin, luteolin-7- glucoside and patulitrin were determined in the dyed fabrics and extracts. The color coordinates and fastness values (washing, perspiration and rubbing) were investigated. Rubbing dry and wet fastnesses are excellent. Dyed organic knitting fabrics were studied calorimetrically and their color coordinates L*, a*, b*, C*, h, K/S, and ∆E* values were given. Yarrow can be used in textile dyeing for yellow dyeing.